Correction to: Fluorescent Silicon Nanorods‑Based Nanotheranostic Agents for Multimodal Imaging‑Guided Photothermal Therapy - Cui, Mingyue; Liu, Sangmo; Song, Bin; Guo, Daoxia; Wang, Jinhua; Hu, Guyue; Su, Yuanyuan; He, Yao (Nano-Micro Letters, 2019)
The utilization of diagnosis to guide/aid therapy procedures has shown great prospects in the era of personalized medicine along with the recognition of tumor heterogeneity and complexity. Herein, a kind of multifunctional silicon-based nanostructure, i.e., gold nanoparticles-decorated fluorescent silicon nanorods (Au@SiNRs), is fabricated and exploited for tumor-targeted multimodal imaging-guided photothermal therapy. In particular, the prepared Au@SiNRs feature high photothermal conversion efficiency (~ 43.9%) and strong photothermal stability (photothermal performance stays constant after five-cycle NIR laser irradiation), making them high-performance agents for simultaneously photoacoustic and infrared thermal imaging. The Au@SiNRs are readily modified with targeting peptide ligands, enabling an enhanced tumor accumulation with a high value of ~ 8.74% ID g−1. Taking advantages of these unique merits, the Au@SiNRs are superbly suitable for specifically ablating tumors in vivo without appreciable toxicity under the guidance of multimodal imaging. Typically, all the mice treated with the Au@SiNRs remain alive, and no distinct tumor recurrence is observed during 60-day investigation. Highlights: 1 A kind of multifunctional silicon-based theranostic agent is fabricated and exploited for imaging-guided tumor-targeted photothermal therapy. 2 The obtained gold nanoparticles-decorated fluorescent silicon nanorods featuring high photothermal conversion performance and good photothermal stability enable a total ablation of tumors and prolong the survival time of mice.